Bioactive Constituents of the Stem Bark of Mitrephora glabra - Li, Chen (2009)
Bioactivity-guided fractionation of the stem bark of Mitrephora glabra yielded nine compounds, comprising three ent-kaurenoids (1–3), five polyacetylenic acids/esters (4–8), and one aporphine alkaloid, liriodenine (9). The structures of the six new compounds (1–3, 5, 7, and 8) were determined by spectroscopic data interpretation. All compounds were evaluated for their inhibitory activities against a panel of cancer cell lines and a battery of microorganisms.